Innovation Capabilities among Young Entrepreneurs in Sabu Raijua: The Roles of Strategic Intuition Capability, Managerial Cognitive Capability, and Absorptive Capacity - Kempa, Sesilya; Sahetapy, Wilma Laura; Andreani, Fransisca; Suprapto, Widjojo; Palumian, Yonathan (Journal of Ecohumanism, 2024)
Sabu Island, a tiny and remote island in East Nusa Tenggara, is a home to young entrepreneurs facing unique challenges to sustain their small businesses in the middle of unfavorable geographic conditions. As small and medium enterprises (SMEs) actors, these young entrepreneurs need to elevate their innovation capability to navigate uncertain and complex environments. This study is aimed to identify the factors influencing innovation capability, focusing on absorptive capacity, managerial cognitive capability, and strategic intuition capability among young entrepreneurs in Sabu Raijua. Using a sample of 244 young SMEs actors and employing Partial Least Squares (PLS) to test the hypotheses, the findings reveal that absorptive capacity and managerial cognitive capability are the strongest predictors promoting innovation capability. In addition, the study highlights that while strategic intuition capability significantly contributes to innovation capability, its effect is relatively less pronounced compared to the other factors. These insights underscore the importance of enhancing cognitive and knowledge absorption mechanisms to elevate the innovative potential of young entrepreneurs in remote regions like Sabu Raijua.